Synthesis of poly(1-hexene)s end-functionalized with phenols - Yanjarappa, Mallinamadugu J.; Sivaram, Swaminathan (Polymer International, 2005)
Electrophilic alkylations of phenol/2,6-dimethylphenol were performed with vinylidene-terminated poly(1-hexene)s using BF3-OEt2 catalyst. Vinylidene-terminated poly(1-hexene)s with M. varying from 400 to 10000 were prepared by bulk polymerization of 1-hexene at 50 to -20 degrees C using Cp2ZrCl2/MAO catalysts. The phenol/2,6-dimethylphenol-terminated poly(1-hexene)s was characterized by NMR (H-1, C-13), UV, IR and vapor phase osmometer (VPO). The isomer distribution (ortho, para and ortholpara) was determined by P-13 NMR using a phosphitylating reagent, namely 2-chloro-1,3,2-dioxaphospholane. The number-average degree of functionality (F-n) > 0.9 with > 95% para selectivity could be achieved using low-molecular-weight oligomers of poly(1-hexene)s. (c) 2005 Society of Chemical Industry.
Keywords: Alkylation; chain-end functionalization; functional poly(olefin)s; metallocene catalysts

Silica-supported bis(imino)pyridyl iron(II) catalyst: nature of the support-catalyst interactions - Ray, Saptarshi; Sivaram, Swaminathan (Polymer International, 2006)
Ethylene polymerizations were performed using silica-supported 2,6-bis[1-(2,6-diisopropylphenylimino) ethyl] pyridine iron(II) dichloride with methylaluminoxane (MAO) as co-catalyst. Silica was calcined at 600, 400 and 200 degrees C under vacuum for 8 h. The effect of calcination temperature of silica on the polymerization activity and the properties of the polymers obtained were examined. Catalyst-support interactions were examined by both a chemical method and XPS. It was observed that upon supporting the catalyst on the surface of silica, there is an increase in the binding energy of the metal center. However, no change in the metal binding energy was observed on supporting the catalyst to silica calcined at different temperatures. Ethylene polymerizations were performed using MAO as co-catalyst. Catalysts were also prepared by first pretreating silica with NIAO, followed by addition of the Fe(II) catalyst and contacting a complex of Fe(II) catalyst-MAO with silica previously calcined at 400 degrees C for 8 h. The results indicate that there is no chemical bonding between the support and the catalyst. (C). 2006 Society of Chemical Industry.
Keywords: bis(imino) pyridyl iron(II) complex; Polyethylene; silica; supported catalyst; XPS

Synthesis and characterization of poly(higher-alpha-olefin)s with a nickel(alpha-diimine)/methylaluminoxane catalyst system: effect of chain running on the polymer properties - Subramanyam, Ummadisetty; Sivaram, Swaminathan (Journal of Polymer Science Part A-Polymer Chemistry, 2007)
Homopolymerization of octadecene-1 at different reaction conditions has been studied. Significant chain running can be seen at higher polymerization temperatures. Interestingly, insertion of octadecene-1 into a sterically hindered nickel-cation/carbon (secondary) bond is observed. The microstructure of the polymer was established using NMR spectroscopy. The effects of chain running on polymer melting, crystallization behavior, and dynamic mechanical thermal properties were studied using DSC and DMTA. The extent of chain running (i.e., 2 omega-, 1,omega-enchainments) decreases with an increase in the carbon number of alpha-olefins. (c) 2006 Wiley Periodicals, Inc.
Keywords: chain running; Crystallization; glass transition; melt transition; nickel (alpha-diimine); NMR; poly(alpha-olefin)s

Synthesis of amphiphilic poly(methyl methacrylate-b-ethylene oxide) copolymers from monohydroxy telechelic poly(methyl methacrylate) as macroinitiator - Dhara, Mahua Ganguly; Baskaran, Durairaj; Sivaram, Swaminathan (Journal of Polymer Science Part A-Polymer Chemistry, 2008)
The synthesis of well-defined poly(methyl methacrylate)-block-poly(ethylene oxide) (PMMA-b-PEO) dibock copolymer through anionic polymerization using monohydroxy telechelic PMMA as macroinitiator is described. Living anionic polymerization of methyl methacrylate was performed using initiators derived from the adduct of diphenylethylene and a suitable alkyllithium, either of which contains a hydroxyl group protected with tert-butyldimethylsilyl moiety in tetrahydrofuran (THF) at -78 degrees C in the presence of LiClO4. The synthesized telechelic PMMAs had good control of molecular weight with narrow molecular weight distribution (MWD). The H-1 NMR and MALDI-TOF MS analysis confirmed quantitative functionalization of chain-ends. Block copolymerization of ethylene oxide was carried out using the terminal hydroxyl group of PMMA as initiator in the presence of potassium counter ion in THF at 35 degrees C. The PMMA-b-PEO diblock copolymers had moderate control of molecular weight with narrow MWD. The H-1 NMR results confirm the absence of trans-esterification reaction of propagating PEO anions onto the ester pendants of PMMA. The micellation behavior of PMMA-b-PEO diblock copolymer was examined in water using H-1 NMR and dynamic light scattering. (C) 2008 Wiley Periodicals, Inc.
Keywords: Anionic polymerization; block copolymers; synthesis

Synthesis of hydroxy-functional PMMA macromonomers by anionic polymerization - Dhara, Mahua Ganguly; Sivaram, Swaminathan; Bhonde, Ramesh R.; Bhagavatula L. V. Prasad (Journal of Macromolecular Science Part A-Pure and Applied Chemistry, 2009)
Living anionic polymerization has been utilized to synthesize hydroxy end-functionalized PMMA macromonomers with styryl or allyl functionalities as the polymerizable end-groups. Protected hydroxy-functionalized alkyl lithium initiators have been used to initiate anionic polymerization of MMA. Subsequently the living chains with protected hydroxyl function have been terminated using 4-vinylbenzyl chloride (4-VBC) or allyl methacrylate (ALMA) to form -hydroxy–styryl and -hydroxy–allyl PMMA, respectively. These protected hydroxy-functionalized PMMA macromonomers have been characterized by GPC and 1H-NMR. Termination using 4-VBC led to 50% functionalization, whereas that using allyl methacrylate led to 100% functionalization of the hydroxy-PMMA.
Keywords: Anionic polymerization; functionalized initiator; Macromonomer

Synthesis of hydroxy-functionalized star-branched PMMA by anionic polymerization - Dhara, Mahua Ganguly; Sivaram, Swaminathan; Baskaran, Durairaj (Polymer Bulletin, 2009)
Living anionic polymerization has been exploited to synthesize hydroxy end-functionalized PMMA star-branched polymers. Protected hydroxy-functionalized alkyl lithium initiators have been used to initiate anionic polymerization of MMA. Subsequently the living chains with protected hydroxyl function have been used to cross-link ethylene glycol dimethacrylate (EGDMA) in order to form star-branched polymers with cross-linked EGDMA core via `arm-first' method. The linear arms and the star molecules have been characterized by (1)HNMR, GPC, and light scattering. Variation in the number of arms with arm molecular weight and cross-linker loading has been studied. Star-branched PMMA-OH with as many as similar to 10 arms could be successfully made. Increased molecular weight of PMMA-OH led to decrease in the number of arms incorporated due to increased steric hindrance on the core. Increase in EGDMA concentration slightly increased the arm incorporation.
Keywords: Anionic polymerization; Star polymers; Star-branched PMMA

Star telechelic poly(L-lactide) ionomers - Kulkarni, Amruta; Lele, Ashish K.; Sivaram, Swaminathan; Rajamohanan, P. R.; Velankar, Sachin; Chatterji, Apratim (Macromolecules, 2015)
Poly(L-lactide) (PLA), a biodegradable and biorenewable polymer, has many excellent properties that are equivalent to those of petroleum-derived plastics such as polystyrene, aromatic polyesters, etc. However, a major disadvantage of PLA which limits its processability is its poor melt elasticity. In this work we explore the possibility of improving the viscoelastic properties of PLA melt by incorporating ionic groups on the polymer. Specifically, we demonstrate the synthesis of star telechelic PLA anionomers by a three-step procedure involving synthesis of Star PIA, converting the hydroxyl end groups into carboxylic acid end groups, and finally converting these into ionic groups. Rheology data showed a dramatic increase in the elasticity of the star telechelic ionomer melts relative to the Star PLA melts. The viscoelasticity of star telechelic ionomers melts could be modulated by varying the number of ionic groups per molecule.

Synthesis and characterization of well-defined random and block copolymers of epsilon-caprolactone with l-lactide as an additive for toughening polylactide: Influence of the molecular architecture - Deokar, Megha D.; Idage, Susheela B.; Idage, Bhaskar B.; Sivaram, Swaminathan (Journal of Applied Polymer Science, 2016)
Well-defined multiarmed star random and block copolymers of epsilon-caprolactone with l-lactide with controlled molecular weights, low polydispersities, and precise numbers of arms were synthesized by the ring-opening polymerization of respective cyclic ester monomers. The polymers were characterized by H-1-NMR and C-13-NMR to determine their chemical composition, molecular structure, degree of randomness, and proof of block copolymer formation. Gel permeation chromatography was used to establish the degree of branching. Star-branched random copolymers exhibited lower glass-transition temperatures (T-g's) compared to a linear random copolymer. When the star random copolymers were melt-blended with poly(l-lactic acid) (PLA), we observed that the elongation of the blend increased with the number of arms of the copolymer. Six-armed block copolymers, which exhibited higher T-g's, caused the maximum improvement in elongation. In all cases, improvements in the elongation were achieved with no loss of stiffness in the PLA blends. (c) 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2016, 133, 43267.
Keywords: biodegradable; copolymers; differential scanning calorimetry; mechanical properties; ring-opening polymerization

Soluble polybenzimidazoles with intrinsic porosity: synthesis, structure, properties and processability - Kumar, Vikas; Chatterjee, Shyambo; Sharma, Pragati; Chakrabarty, Suman; Avadhani, Chilukuri V.; Sivaram, Swaminathan (56Journal of Polymer Science Part A-Polymer Chemistry, 2018)
We have explored two novel comonomers, namely, 4,16-dicarboxyl[2.2]paracyclophane and 5,5,6,6-tetraamino-3,3,3,3-tetramethyl-1,1-spirobi[indane], for the synthesis of co-polybenzimidazoles (co-PBIs) with intrinsic porosity. Both these monomers possess twisted structures that can lead to awkward macromolecular shapes that cannot pack efficiently. The consequences of introducing these two monomers on the structure and properties of PBIs are reported. The random copolymers synthesized are amorphous and possess glass transition temperatures (T(g)s) greater than 400 degrees C. T-g decreases with increasing comonomer content indicating an increase in fractional free volume. The copolymers have low surface area. TEM and BET measurements show evidence of mesopore formation. The copolymers show significant carbon dioxide adsorption. Single chain molecular dynamics simulation of 24-mer repeat units shows intramolecular void spaces arising as a result of distorted polymer chain with reduced conformational mobility. These studies define a new synthetic strategy for bottoms-up synthesis of PBIs with intrinsic porosity. (c) 2018 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2018, 56, 1046-1057

Separator membranes for lithium-sulfur batteries: design principles, structure, and performance - Gupta, Aritrajit; Sivaram, Swaminathan (Energy Technology, 2019)
Improvement in electrical energy storage systems is one of the most recent research topics of great academic and industrial interest. Lithium-sulfur (Li-S) battery systems offer a theoretical energy density an order of magnitude larger than the popular Li-ion batteries. The principle of working, inherent challenges in utilizing this system for commercial applications, and the various approaches taken to address these challenges are herein discussed in detail. The polysulfide shuttle effect is a major concern that deteriorates electrochemical performance in this system. In the recent past, electrodes have been intricately engineered to tackle this problem. However, more recently, the focus has shifted to the critical role of the separator. Modifying conventional separators or fabricating novel structures to enhance the cell performance appears to be a more feasible option. Some design principles that are critical to the functioning of a separator in Li-S batteries, namely physisorption, chemisorption, and electrostatic repulsion, are discussed. Many recent papers proposed novel cell configurations with specifically designed functional separators. These reports are classified according to three design principles, analyzed critically, and compared with a view to assess their relative merits and efficacy. Some thoughts on the future directions in the development of an efficient separator are described.
Keywords: lithium-sulfur batteries; polysulfides; rechargeable batteries; separators; shuttle effect

Solvent-free hydroxylation of unactivated C-H bonds in small molecules and macromolecules by a Fe complex - Chatterjee, Debasmita; Sajeevan, Amritha; Jana, Sandipan; Birajdar, Rajkumar S.; Chikkali, Samir H.; Sivaram, Swaminathan; Sen Gupta, Sayam (ACS CATALYSIS, 2024)
Keywords: Ball milling; solid-state C-H hydroxylation

Shola: a 3D porous hydrophobic-oleophilic lignocellulosic material for efficient oil/water separation - Mondal, Keya; Advani, Kushagra; Ghosh, Snigdha; Shanmugnathan, Kadhiravan; Kulsi, Goutam; Sivaram, Swaminathan; Sen Gupta, Sayam (Journal of Materials Chemistry A, 2025)
Transitioning from the fossil fuel era to a sustainable future requires increasing adoption of high-performing renewable materials in industrial applications. Natural polymers derived from lignocellulosic materials are often considered more environmentally friendly than their petroleum-based synthetic analogs. Aeschynomene aspera, commonly known as Shola, has been found to be a large source of amorphous cellulose and a useful sorbent for the removal of oil from water. The Shola pith, the pure white inner stem, is rich in cellulose and has an exquisite three-dimensional and hierarchical porous architecture created by nature. The pith consists of about 70 wt% cellulose as the main chemical component, which is much higher than what is found in other lignocellulosic sources. In addition, the pith has about 12 wt% hemicellulose, 2-3 wt% pectin, 10 wt% lignin, 2.5 wt% wax, and 2 wt% protein as other chemical components. It was observed that water has a high contact angle (135 degrees) on the surface of the pith, while oil droplets instantly spread on the surface, indicating excellent hydrophobic-oleophilic properties. Further studies reveal that the Shola pith exhibits a fast and high sorption capacity of 40-60 g/g for various oils and organic liquids. Silicone oil shows a sorption capacity of about 166 g/g. When applied to oil-floating-over-water, the Shola pith exhibits high selectivity for oil over water; almost all oil on the surface could be removed, leaving no trace of oil on the water surface. The Shola pith can also efficiently separate oil from an oil-in-water emulsion. This behavior is unprecedented in natural sorbents. The used material sorbs a considerable volume of the oil even after the 7th cycle. Furthermore about 95% of sorbed oil could be recovered from the material by solvent extraction. This study reveals for the first time some of the unique and interesting properties of Shola, a widely found biomass native to the eastern parts of the Indian subcontinent, and opens up possibilities of exploiting it for valuable applications.